What ʻĪsá Ibn Hishām told us, or, A period of time - Muwayliḥī, Muḥammad (Library of Arabic literature., 2015)
With What?Isa ibn Hisham Told Us, the Library of Arabic Literature brings readers an acknowledged masterpiece of early 20th-century Arabic prose. Penned by the Egyptian journalist Muhammad al-Muwaylihi, this exceptional title was first introduced in serialized form in his family's pioneering newspaper Misbah al-Sharq (Light of the East), on which this edition is based, and later published in book form in 1907. Widely hailed for its erudition and its mordant wit, What?Isa ibn Hisham Told Us was embraced by Egypt's burgeoning reading public and soon became required reading for generations of E.